EVALUATION OF THE ACTIVE LABOR MARKET POLICIES IN THE REPUBLIC OF SRPSKA - Tomić, Velinka (Journal of Economic Development, Environment and People, 2021)
This paper discusses the methods of evaluating active labor market policy. In addition, an important aspect of the analysis, conducted in this paper, concerns the assessment of the relative success of these measures in the case of the Republic of Srpska. The statistical analysis evaluated the success of three choosen projects implemented in the Republic of Srpska. A major problem in evaluating the effectiveness of individual measures is inadequate IT support. The unemployed persons are not monitored for all the characteristics that play a significant role in determining the target groups for particular measures. The measures are primarily intended for young people and categories related to the recent war conflicts in the former Yugoslavia. The relative assessment of the success of individual measures has confirmed that these measures are not greatly influenced by raising general employment, but these programs, at least to some extent, alleviate the problem of unemployment and improve the position of the hard-to-employ categories of the unemployed persons.